CMEs and SEPs During November‐December 2020: A Challenge for Real‐Time Space Weather Forecasting. Issue 5 (27th April 2022) - Palmerio, Erika; Lee, Christina O.; Mays, M. Leila; Luhmann, Janet G.; Lario, David; Sánchez‐Cano, Beatriz; Richardson, Ian G.; Vainio, Rami; Stevens, Michael L.; Cohen, Christina M. S.; Steinvall, Konrad; Möstl, Christian; et al.
Abstract: Predictions of coronal mass ejections (CMEs) and solar energetic particles (SEPs) are a central issue in space weather forecasting. In recent years, interest in space weather predictions has expanded to include impacts at other planets beyond Earth as well as spacecraft scattered throughout the heliosphere. In this sense, the scope of space weather science now encompasses the whole heliospheric system, and multipoint measurements of solar transients can provide useful insights and validations for prediction models. In this work, we aim to analyze the whole inner heliospheric context between two eruptive flares that took place in late 2020, that is, the M4.4 flare of 29 November and the C7.4 flare of 7 December. This period is especially interesting because the STEREO‐A spacecraft was located ∼60° east of the Sun–Earth line, giving us the opportunity to test the capabilities of "predictions at 360°" using remote‐sensing observations from the Lagrange L1 and L5 points as input. We simulate the CMEs that were ejected during our period of interest and the SEPs accelerated by their shocks using the WSA‐Enlil‐SEPMOD modeling chain and four sets of input parameters, forming a "mini‐ensemble." We validate our results using in situ observations at six locations, including Earth and Mars. We find that, despite some limitations arising from the models' architecture and assumptions, CMEs and shock‐accelerated SEPs can be reasonably studied and forecast in real time at least out to several tens of degrees away from the eruption site using the prediction tools employed here. Plain Language Summary: Coronal mass ejections (CMEs) and solar energetic particles (SEPs) are phenomena from the Sun that are able to cause significant disturbances at Earth and other planets. Reliable predictions of these events and their effects are among the major goals of space weather forecasts, which aim to tackle all processes related to solar activity that can endanger human technology and society. In recent years, the breadth of space weather science has started to encompass other locations than Earth, ranging from all solar system planets to spacecraft scattered throughout space. In this work, we test our current capabilities in predicting space weather events in the inner solar system (i.e., within the orbit of Mars) for a period in late 2020. We use a chain of models that are able to simulate the background solar wind as well as transient phenomena such as CMEs and SEPs, and compare our results with spacecraft measurements from six well‐separated locations, including Earth and Mars. We find that our current forecasting tools, despite their limitations, can successfully provide reasonable predictions of both CMEs and SEPs, especially out to several tens of degrees around the corresponding eruption source region on the Sun. Key Points: We model the inner heliospheric context between the two eruptive flares of 29 November and 7 December 2020 using the WSA‐Enlil‐SEPMOD modeling chain Coronal mass ejection (CME) input parameters are obtained using remote‐sensing observations from Earth and STEREO‐A, located near the L5 point The modeling setup used in this work can provide useful CME and shock‐accelerated solar energetic particle predictions in real‐time forecasts